A branched galactoglucan with flexible chains from the basidioma of Macrolepiota albuminosa (Berk.) Pegler. (15th January 2022) - Wang, Yu-Xiao; Xin, Yue; Huang, Xiao-Jun; Yin, Jun-Yi; Nie, Shao-Ping
Graphical abstract: Highlights: A branched galactoglucan was purified from alkali-extracted polysaccharides from M. albuminosa . It exhibited a random coil conformation with a molecular weight of 210 kDa. Its steady flow behavior was highly dependent on concentration. The structure of alkali-extracted polysaccharides from M. albuminosa was given for the first time. Abstract: A homogeneous galactoglucan was purified from the alkali-extracted polysaccharides from the basidioma of Macrolepiota albuminosa by gradient ethanol precipitation, whose proposed structure was given for the first time. Results showed it had a molecular weight of 210 kDa, and mainly consisted of glucose and galactose. There were abundant filaments, randomly distributed sheet-like and flaky appearance in its surface by SEM observation. Its backbone comprised β-(1 → 6)-Glc p, α-(1 → 6)-Gal p and β-(1 → 3, 6)-Glc p residues at 4:1:1, terminated by β-(1 → 3)-Glc p and T -Glc p residues. Rheological measurements suggested its steady flow behavior was highly dependent on concentrations. Newtonian behavior was evident at low concentrations, whereas pseudoplastic behavior was observed at high concentrations. Besides, the X-ray diffraction patterns proved the presence of amorphous structure. The conformational parameters were detected by HPSEC-MALLS-RI, revealing a random coil conformation in NaNO3 aqueous solution. This work provides a theoretical basis for the application of polysaccharides from M. albuminosa in food- and drug-based therapies.